A group intervention to improve quality of life for people with advanced dementia living in care homes: the Namaste feasibility cluster RCT - Katherine Froggatt (Health Technology Assessment, 2020)
Background: People with advanced dementia who live and die in nursing homes experience variable quality of life, care and dying. There is a need to identify appropriate, cost-effective interventions that facilitate high-quality end-of-life care provision. Objectives: To establish the feasibility and acceptability to staff and family of conducting a cluster randomised controlled trial of the Namaste Care intervention for people with advanced dementia in nursing homes. Design: The study had three phases: (1) realist review and (2) intervention refinement to inform the design of (3) a feasibility cluster randomised controlled trial with a process evaluation and economic analysis. Clusters (nursing homes) were randomised in a 3 : 1 ratio to intervention or control (usual care). The nature of the intervention meant that blinding was not possible. Setting: Nursing homes in England providing care for people with dementia. Participants: Residents with advanced dementia (assessed as having a Functional Assessment Staging Test score of 6 or 7), their informal carers and nursing home staff. Intervention: Namaste Care is a complex group intervention that provides structured personalised care in a dedicated space, focusing on enhancements to the physical environment, comfort management and sensory engagement. Main outcome measures: The two contender primary outcome measures were Comfort Assessment in Dying – End of Life Care in Dementia for quality of dying (dementia) and Quality of Life in Late Stage Dementia for quality of life. The secondary outcomes were as follows: person with dementia, sleep/activity (actigraphy), neuropsychiatric symptoms, agitation and pain; informal carers, satisfaction with care at the end of life; staff members, person-centred care assessment, satisfaction with care at the end of life and readiness for change; and other data – health economic outcomes, medication/service use and intervention activity. Results: Phase 1 (realist review; 86 papers) identified that a key intervention component was the activities enabling the development of moments of connection. In phase 2, refinement of the intervention enabled the production of a user-friendly 16-page A4 booklet. In phase 3, eight nursing homes were recruited. Two homes withdrew before the intervention commenced; four intervention and two control homes completed the study. Residents with advanced dementia (n = 32) were recruited in intervention (n = 18) and control (n = 14) homes. Informal carers (total, n = 12: intervention, n = 5; control, n = 7) and 97 staff from eight sites (intervention, n = 75; control, n = 22) were recruited over a 6-month period. Recruitment is feasible. Completion rates of the primary outcome questionnaires were high at baseline (100%) and at 4 weeks (96.8%). The Quality of Life in Late Stage Dementia was more responsive to change over 24 weeks. Even where economic data were missing, these could be collected in a full trial. The intervention was acceptable; the dose varied depending on the staffing and physical environment of each care home. Staff and informal carers reported changes for the person with dementia in two ways: increased social engagement and greater calm. No adverse events related to the intervention were reported. Conclusions: A subsequent definitive trial is feasible if there are amendments to the recruitment process, outcome measure choice and intervention specification. Future work: In a full trial, consideration is needed of the appropriate outcome measure that is sensitive to different participant responses, and of clear implementation principles for this person-centred intervention in a nursing home context. Trial registration: Current Controlled Trials ISRCTN14948133. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 24, No. 6. See the NIHR Journals Library website for further project information.